Distribution of Potassium Fractions in Soils under Different Land Uses in Coastal Region of Raigad District, Maharashtra - S.Y. Rakhonde; D.G. Jondhale; M.R. Wahane; D.K. Borse; S.B. Dodake; N.H. Khobragade; M.C. Kasture; Jagdish Prasad (Journal of the Indian Society of Soil Science, 2026)
The distribution of different potassium fractions in nine typical pedons, associated with different land uses (grassland, paddy, fallow land) in the coastal region of Raigad district, Maharashtra were studied. The soils were clay loam to silt loam in texture and their pH varied from 5.05 to 6.60 electrical conductivity from 0.15 and 20.10 dS m–1. The surface horizon of grassland had higher organic carbon (> 20 g kg–1) than the paddy-growing soil and in general, soil organic carbon showed positive correlation with lattice and total K, but was inversely related to exchangeable K. Fallow land showed higher water-soluble, exchangeable and available K in the surface horizon than the cultivated soils. Soil pH had inverse relationship with lattice and total K, while it was positively related to available K. Clay content was inversely related to nonexchangeable, lattice, and total K, whereas, silt content had a negative association with water-soluble, available K, but a positive relationship with lattice K. In contrast, sand content had a strong positive relationship with water-soluble and available K. Water-soluble potassium showed a strong positive correlation with all K-forms barring lattice K. Exchangeable K and available K had significant positive relationship with available K and non-exchangeable K. There was a positive correlation between nonexchangeable and total K, lattice and total K. Amongst the different K fractions, total K followed by lattice K, was highest in all the land uses. In paddy field, the order for K fractions was as total K > lattice K > available K > non-exchangeable K > exchangeable K > water-soluble K while the order for other fractions differed in soils of grassland and fallow land.